Knowledge, Fear, and Stigma Towards COVID-19 among Healthcare Providers Working at Federal Territories of Kuala Lumpur and Putrajaya Health Department Facilities - Azmi, Wafi Mardhiah; Hisham, Shairyzah Ahmad; Salamat, Nur Aini (International Journal of Human and Health Sciences (IJHHS), 2022)
Objective. This study was conducted to assess knowledge, fear and presence of stigma towards COVID-19, to assess the relationship of these parameters with various sociodemographic backgrounds of healthcare providers (HCPs), and to establish predictors of knowledge, fear and stigma about COVID-19 among HCPs. Methods. This was a cross-sectional survey utilising a self-administered online questionnaire conducted between 1st April and 31st May 2021. The study involved 200 HCPs who worked at the Federal Territories of Kuala Lumpur and Putrajaya Health Department facilities. The questionnaire used in the study was adopted and adapted from previous studies and underwent simple validity testing. Results. This study has successfully established that HCPs working in this area have good knowledge of COVID-19 with a low degree of fear and stigma towards COVID-19. A weak but statistically significant correlation between knowledge and fear was also established (r = 0.211, P < 0.05). HCPs working in tertiary care facilities had significantly higher knowledge levels on COVID-19 compared to those working in primary care facilities. Meanwhile, female and married respondents were shown to be more fearful of COVID-19 than their male and single counterparts (P < 0.05); HCPs in the dentistry and pharmacy professions were statistically more fearful of COVID-19 than those in the medical professions. Being female and having the highest education level of secondary education or lower, were more likely to show the presence of stigma than males and respondents with tertiary education (P < 0.05). This study also found that direct involvement in the management of COVID-19 patients was a predictor of a good knowledge level. Previous exposure to COVID-19 was also a significant predictor of fear while predictors for the presence of stigma were gender and highest educational attainment. Among those who obtained COVID-19 information via the internet, the acceptance of the COVID-19 vaccine was widely distributed. Conclusion. This study suggests that an increase of knowledge on the disease could be necessary to reduce the fear and stigma associated with COVID-19 among HCPs. Steps to ensure effective regular delivery of updated information regarding the disease should be explored. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S39